2020
DOI: 10.1596/1813-9450-9444
|View full text |Cite
|
Sign up to set email alerts
|

Women's Legal Rights and Gender Gaps in Property Ownership in Developing Countries

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Gender gaps are larger among marginalized and disadvantaged population groups, and larger in rural than in urban areas (Ibid). Several studies have found that women who own a house, land or other property are doing better (Gaddis et al, 2020), as is echoed by the research participant Shahnaz in the quote at the start of this section. They have more bargaining power (Agarwal, 1994), are less likely to live in poverty, have more decision‐making power (Mishra & Sam, 2016), and are less likely to stay in abusive relationships (Oduro & van Staveren, 2015).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Gender gaps are larger among marginalized and disadvantaged population groups, and larger in rural than in urban areas (Ibid). Several studies have found that women who own a house, land or other property are doing better (Gaddis et al, 2020), as is echoed by the research participant Shahnaz in the quote at the start of this section. They have more bargaining power (Agarwal, 1994), are less likely to live in poverty, have more decision‐making power (Mishra & Sam, 2016), and are less likely to stay in abusive relationships (Oduro & van Staveren, 2015).…”
Section: Introductionmentioning
confidence: 80%
“…Sykes and Sykes (2005) showed a positive relationship between age, income and interest, dividend and rental income with the relative odds of home ownership. In most developing countries, women acquire ownership of property mainly through two pathways: either through inheritance, or through marriage (Gaddis et al, 2020).…”
Section: Home Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Equitable treatment for women under the law facilitates their access to financial services and increases their financial inclusion. However, in many countries, women still face legal restrictions which preclude them from owning assets, seeking employment or operating a business (UN Women, 2019; Gaddis et al , 2020; World Bank, 2021). Studies indicate that weak or limiting legislation surrounding family, gender-based violence and financial opportunities obstruct women’s empowerment.…”
Section: Sociological Factors Lack Of Empowerment Employer Choice And...mentioning
confidence: 99%
“…A recent study using data from forty-one developing countries shows that gender gaps in property ownership among couples is correlated with discriminatory laws related to property ownership, inheritance rules, marital regimes, and workplace discrimination. 6 Inegalitarian distribution of economic resources can rob women of agency, voice, self-confidence, and self-esteem. These effects are most keenly manifest within the household.…”
mentioning
confidence: 99%